Progesterone, via yes‐associated protein, promotes cardiomyocyte proliferation and cardiac repair. (12th October 2020) - Lan, Cong; Cao, Nian; Chen, Caiyu; Qu, Shuang; Fan, Chao; Luo, Hao; Zeng, Andi; Yu, Cheng; Xue, Yuanzheng; Ren, Hongmei; Li, Liangpeng; Wang, Hongyong; et al.
Abstract: Objectives: The mechanisms responsible for the postnatal loss of mammalian cardiac regenerative capacity are not fully elucidated. The aim of the present study is to investigate the role of progesterone in cardiac regeneration and explore underlying mechanism. Materials and Methods: Effect of progesterone on cardiomyocyte proliferation was analysed by immunofluorescent staining. RNA sequencing was performed to screen key target genes of progesterone, and yes‐associated protein (YAP) was knocked down to demonstrate its role in pro‐proliferative effect of progesterone. Effect of progesterone on activity of YAP promoter was measured by luciferase assay and interaction between progesterone receptor and YAP promoter by electrophoretic mobility shift assay (EMSA) and chromatin immunoprecipitation (ChIP). Adult mice were subjected to myocardial infarction, and then, effects of progesterone on adult cardiac regeneration were analysed. Results: Progesterone supplementation enhanced cardiomyocyte proliferation in a progesterone receptor‐dependent manner. Progesterone up‐regulated YAP expression and knockdown of YAP by small interfering RNA reduced progesterone‐mediated cardiomyocyte proliferative effect. Progesterone receptor interacted with the YAP promoter, determined by ChIP and EMSA; progesterone increased luciferase activity of YAP promoter and up‐regulated YAP target genes. Progesterone administration also promoted adult cardiomyocyte proliferation and improved cardiac function in myocardial infarction. Conclusion: Our data uncover a role of circulating progesterone withdrawal as a novel mechanism for the postnatal loss of mammalian cardiac regenerative potential. Progesterone promotes both neonatal and adult cardiomyocyte proliferation by up‐regulating YAP expression. Abstract : Progesterone promotes cardiomyocyte proliferation by transcriptional activation of YAP.